Sovietų Sąjungos žurnalistų delegacijos vizitas į Suomiją ir Baltijos šalis 1937 metais: delegacijos vadovo Boriso Michailovo pranešimas Stalinui ir Molotovui - Butkus, Zenonas; llmjärv, Magnus (Lietuvos istorijos studijos, 2010)
The article presents the leader's of the USSR journalists' delegation, Michailov's, report to Stalin and Molotov on the July 19-August 10, 1937 visit to Finland, Estonia, Latvia, and Lithuania, which was found in the Russian State Archive for Social and Political History, Molotov's Stock (f. 82, i. 2, r. 1020, p. 4-16). The document presented might seem to be complete propaganda, bloated with class struggle, and in general full of Marxist clichés. It is, however, an authentic testimony of the attitude formed by those in the highest circles of Soviet authorities towards the Baltic countries. The attitude became of high importance to those countries' fate in just a few years. Soviet clichés notwithstanding, the document also reflects the internal and international situation of the countries. The visit itself was not just an ordinary fact of cultural ties but an action motivated by international political considerations, which has not been addressed in historical works yet.The aim of the visit of the delegation under the lead of Michailov was to collect information about the Baltic countries, which was outside the reach through normal diplomatic channels. First of all, an attempt was made to perceive the mood of the population and to foresee any possible changes in the course of a potential war. There was also a goal to shift the attitude in favour of the Soviet Union. An attempt was made to show that the ongoing repressions did not hinder its active foreign policy, and did not prevent it from having close relations with the neighbouring countries. This visit, to a certain extent, could also have been a demonstration against Germany - an attempt was made to make it understand that the Soviets were influential in the Baltic region, and therefore, the expansionary politics had to be done in coordination with them.The USSR journalists were favourably welcomed in the Baltic countries. They were received by the official representatives of the authorities, and by social and cultural organizations. The report as a historical source is supplemented by the memoirs of the member of the Soviet delegation Tichonov, published in 1964. Both sources as well as the press reports indicate that the welcome of the delegation was the warmest in Lithuania - a large part of its politicians as well as influential intellectuals still believed that Moscow would help Lithuania to regain Vilnius and retain Klaipėda. Left-wing intellectuals of the Baltic countries, among whom it is already possible to notice Justas Paleckis and Johanes Vares-Barbarus, leaders-to-be of the puppet governments of the 1940 occupation in Lithuania and Estonia, actively adjoined the delegations. This fact alone already testifies the after-effects of the visit.